PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI BENDUNGAN SEMARANG - Khofifatur Rohmah; Joko Siswanto (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The study aimed to investigate the impact of the project-based learning model on the academic performance of fourth-grade science students. The research focused on all 27 students in class IV A at Bendungan State Elementary School, using non-probability sampling. It employed a quantitative approach with a one-group pretest-posttest design and utilized multiple-choice questions as the assessment tool. Normality tests confirmed that both pretest and posttest data were normally distributed. The paired sample t-test yielded a significant result (sig. 0.000), indicating that the project-based learning model had a positive influence on student learning outcomes. Additionally, the N-Gain test revealed a medium level of improvement in student scores, ranging from 0.6366 to 0.7.